Heat Stress Response in Ruditapes Decussatus: Transcriptional Regulation of Key Pathways and Novel SNPs in Antioxidant Genes - Dimitrios K. Papadopoulos; Basile Michaelidis; Ioannis A. Giantsis (Ecology and Evolution, 2025)
ABSTRACT Global warming significantly impacts coastal zones, particularly affecting ectothermic inhabitants such as bivalve mollusks. This study evaluates the response of the grooved carpet shell clam Ruditapes decussatus (Linnaeus, 1758) to increasing temperatures (22.5°C, 24.5°C, 26.5°C) over 25 days through the transcription of key genes involved in antioxidant defense [Cu‐Zn superoxide dismutase (Cu‐Zn sod), catalase, metallothionein], anti‐apoptotic procedures [b‐cell lymphoma 2 (bcl2)], and energy metabolism [pyruvate kinase (pk), phosphoenolpyruvate carboxykinase (pepck)]. Additionally, the genes catalase and Cu‐Zn sod were characterized for the first time, and along with the metallothionein gene, were sequenced in heat‐resilient and heat‐susceptible individuals to identify polymorphisms potentially associated with thermal tolerance. At 22.5°C, clams showed a delayed increase in glycolytic flux and a gradual up‐regulation of antioxidant and anti‐apoptotic mechanisms. At 24.5°C and 26.5°C, a strong initial stress response resulted in equally high mortality during the early days of exposure. Subsequently, clams appeared to shift toward a reduced energy metabolism, with mildly upregulated antioxidant defenses and anti‐apoptotic activity. With prolonged exposure, there was evidence of enhanced aerobic glycolysis, antioxidant, and anti‐apoptotic responses at these temperatures. However, increased pepck transcription on days 12 and 25 suggests that metabolic demands may have exceeded aerobic capacity, potentially triggering apoptotic processes at 26.5°C. Clams at 24.5°C maintained aerobic capacity upon the final day, also engaging anaerobic pathways to meet energy demands. Eventually, three SNPs were statistically correlated with heat resilience. These included one non‐synonymous SNP in catalase, one SNP in the 3′ untranslated region (3′UTR) of metallothionein, and one synonymous SNP in Cu‐Zn sod. These findings underscore the sensitivity of R. decussatus populations from the northeastern Mediterranean to persistent thermal stress and reveal several polymorphisms in antioxidant genes with potential adaptive significance. However, the limited sample size and the weak correlations observed in some cases highlight the need for further research to clarify the relationship between these polymorphisms and thermal resilience.